2018
DOI: 10.1080/15412555.2018.1476475
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophilic Inflammation in the Pathogenesis of Chronic Obstructive Pulmonary Disease

Abstract: Current paradigms of chronic obstructive pulmonary disease (COPD) treatment suggest stratifying patients by their symptoms, utilising three main drug classes, but it is unclear if this approach will substantially alter the progression of the disease in the long term. More treatment options are needed which target the underlying pathology of the condition. Whilst many inflammatory cells are implicated in COPD, the neutrophil is by far the most abundant and has been extensively associated with disease pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 192 publications
(125 reference statements)
1
36
0
Order By: Relevance
“…Caused mostly by exposure to environmental factors such as tobacco smoke and pollution [138], COPD also depends on underlying genetic predispositions [139]. As with CF, lung disease in COPD is characterized by a heavy neutrophil component [140], with extracellular NE being associated with severity of disease and exacerbations [141][142][143]. In addition, it was observed by Chrysanthopoulou that exposure to cigarette smoke induces NET formation which contributes to lung fibrosis [144].…”
Section: Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%
“…Caused mostly by exposure to environmental factors such as tobacco smoke and pollution [138], COPD also depends on underlying genetic predispositions [139]. As with CF, lung disease in COPD is characterized by a heavy neutrophil component [140], with extracellular NE being associated with severity of disease and exacerbations [141][142][143]. In addition, it was observed by Chrysanthopoulou that exposure to cigarette smoke induces NET formation which contributes to lung fibrosis [144].…”
Section: Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) COPD is a chronic inflammatory lung disease with persistent airflow obstruction that is presented clinically as emphysema, obstructive bronchitis, exacerbation and lung function decline [124]. COPD continues to be a leading cause of morbidity and mortality worldwide, with an estimated prevalence of 328 million people already being the third leading cause of death worldwide [125].…”
Section: Granulocyte-targeted Therapies For Asthmamentioning
confidence: 99%
“…Smoking can release both GM-CSF and granulocyte colony-stimulating factor (G-CSF) from epithelial cells and macrophages, which can stimulate granulocyte production, release and survival [127]. Neutrophils in the peripheral blood bind to endothelial cells via E-selectin and are drawn to the airway by neutrophil chemoattractants, such as CXC ligand-1 (CXCL1), CXCL5, CXCL8 and LTB 4 [124]. Secreted granule proteins and serine proteases from neutrophils contribute towards alveolar destruction, inflammation and oxidative stress.…”
Section: Granulocyte-targeted Therapies For Asthmamentioning
confidence: 99%
“…Neutrophilic inflammation in airways is considered central to the pathogenesis of COPD, regardless of the clinical phenotype, severity of disease, rapidity of lung function decline, and age of onset [14]. It was found that the proinflammatory cytokine IL-17 played a crucial role in COPD progression [15,16].…”
Section: Introductionmentioning
confidence: 99%